Semi-empirical many-body formalism of optical absorption in nanosystems and molecules. (July 2021) - Honet, Antoine; Henrard, Luc; Meunier, Vincent
Abstract: A computationally efficient Green's function approach is developed to evaluate the optical properties of nanostructures within a semi-empirical Hubbard model. A GW formalism is applied on top of a tight-binding and mean-field approach. The use of the GW approximation includes key parts of the many-body physics that govern the optical response of nanostructures and molecules subjected to an external electromagnetic field and that is not included in the mean-field approximation. Such description of the electron-electron correlation yields computed spectra that compare significantly better with experiment for a subset of polycyclic aromatic hydrocarbons (PAHs) considered for illustrative purpose. More generally, the method is applicable to any structure whose electronic properties can be described in first approximation within a mean-field approach and is amenable for high-throughput studies aimed at screening materials with desired optical properties. Graphical abstract: Image, graphical abstract